(untitled) (Indian Journal of Animal Production and Management, 2024)
This research paper evaluates the production performance and economic viability of Khaki Campbell ducks in backyard farming systems at NICRA-adopted flood-prone village in the Darrang district of Assam. The study investigates key productivity metrics such as egg production rates, growth performance, and survival rates, alongside economic factors including input costs, labor requirements, and market returns. The integration of Khaki Campbell ducks, renowned for their high egg yield and resilience, is explored as a sustainable agricultural practice that aligns with the objectives of the National Innovations in Climate Resilient Agriculture (NICRA) project. Findings indicate that Khaki Campbell ducks perform well in backyard systems, with notable egg production and robust growth. The mean body weight at 30 weeks was 1.82±8.4 kg, and the average age at first egg was 163±4.3 days. Throughout the study period, the mean egg production was 185.5±5.1, and the mean mortality rate was 12.5%. Economically, the practice is viable with a B:C ratio of 2.07, showing favorable returns compared to the investment and labor involved. The research highlights the potential for these ducks to enhance household income and nutritional security, contributing to greater agricultural resilience against climate variability. These insights provide valuable guidance for policymakers and rural development initiatives aiming to promote sustainable and climate-resilient agriculture in similar regions.